(untitled) (Revista Apotheke, 2026)
This article analyses artistic residency initiatives that support the development of projects and research of visual artists. We propose to consider the creative spaces of artistic residencies as temporary studios, understood as places of encounter and dialogue among artists, critics and curators. We begin by addressing the strategies behind the creation of Bolsa Pampulha (MG) and Bolsa Produção para Artes Visuais (PR), taking into consideration that these are projects carried out in urban centers through cultural institutions. We then analyze the experiences of Residência Sergius Erdelyi and Residência Fim do Mundo, both projects carried outside capital cities, with the aim of providing an immersive experience that involves community engagement and local memories as part of the process.